Parametric study of passive piles subjected to adjacent surcharge load in extensively deep soft soil - Yi, Shixuan; Gu, Meixiang (Frontiers in Materials, 2022)
This study applied the three-dimensional finite different method (FDM) to model a single pile subjected to passive loading due to a new embankment in extensively soft soil. Four important parameters (pile bending stiffness, distance between the long edge of the loading area and the pile (D), embankment height, and cushion thickness) were investigated to evaluate their effects on the deformations and stresses on the passive pile. The displacement of the pile shaft, vertical displacement of the foundation soil, excess pore water pressure (EPWP), and lateral earth pressure were analyzed. The numerical results showed that the lateral displacement of the pile was significantly affected by the four parameters. The maximum lateral displacement decreased dramatically for the high-stiffness pile. A cushion thickness of <1 m slightly increased the lateral displacement of the pile. Increased D value and decreased embankment height significantly reduced the lateral displacement of the pile. The vertical displacement of the loading area was unaffected by pile stiffness. The distribution shape of the vertical displacement was close to symmetrical with increasing D value. The embankment height and cushion thickness significantly affected the vertical displacement. Due to the low permeability of the foundation soil and short construction time, the EPWP was not fully dissipated with varying pile stiffness and D values. A decreased pile stiffness increased the lateral earth pressure at the pile, while increasing embankment height and cushion thickness increased the lateral earth pressure.